NEW EMBO MEMBER’S REVIEW: Role of integrins in regulating epidermal adhesion, growth and differentiation - Watt, Fiona M. (Oxford University Press, 2002)
Mammalian epidermis is renewed throughout life by proliferation of a multipotential stem cell population and terminal differentiation of stem cell progeny. In recent years, extracellular matrix receptors of the integrin family have been identified as important regulators of epidermal homeostasis, influencing the balance between stem cell renewal and differentiation. Integrin expression is altered when the epidermis is damaged or diseased, and there is good evidence that specific integrins can contribute positively or negatively to pathogenesis. In this review I summarize what is known about the expression and function of epidermal integrins, and highlight the challenges for future research.